Relation between left ventricular function and oxidative stress in patients undergoing bypass surgery. Issue 3 (1st March 1998) - De Vecchi, E; Pala, M G; Di Credico, G; Agape, V; Paolini, G; Bonini, P A; Grossi, A; Paroni, R
Abstract : Objective: To determine whether preoperative left ventricular ejection fraction (LVEF) is related to the degree of myocardial oxidative stress during bypass surgery in man. Design: Observational study. Setting: Tertiary care centre. Patients and interventions: 31 patients (LVEF range was 20% to 68%) undergoing elective coronary bypass surgery with blood cardioplegic reperfusion were studied. Arterial and coronary sinus blood was collected before aortic cross clamping (T0) and at 0 (T1), 15 (T2), and 30 (T3) minutes after unclamping. Transmural left ventricular biopsies were also obtained from 15 patients at T0 and at T1. Main outcome measures: Glutathione and adenine nucleotides were measured in myocardial biopsies, while coronary sinus–artery differences for glutathione, nucleotides, and products of lipid peroxidation were calculated from blood specimens. Creatine kinase (myocardial band; CK-MB) was measured in plasma at four and 12 hours after operation. Results: Myocardial glutathione and adenine nucleotides were correlated (p < 0.02) with preoperative LVEF both at T0 ( r  = 0.909 and 0.672) and T1 ( r  = 0.603 and 0.605). Oxidised glutathione released from the heart during reperfusion was inversely correlated with LVEF ( r  = −0.448, −0.466, and −0461 at T1, T2, and T3, p < 0.01), while reduced glutathione ( r  = 0.519 and 0.640 at T1 and T2) and glutathione redox ratio ( r  = 0.647, 0.714, 0.645, and 0.702 at T0, T1, T2, and T3) showed a direct correlation (p < 0.01). Lipid peroxidation at T1 was negatively related to LVEF ( r  = −0.492). CK-MB was also negatively related to LVEF ( r  = −0.440 at 4 h and −0.462 at 12 h). Conclusions: The capacity to counterbalance oxidative burst following ischaemia and reperfusion appears to be related to the functional ability of the heart.